(A Study on The Effect of aw Towards The Crispness and Linear Expansion of Fish Crackers) - M Maman Rohaman; Dadang Supriatna (Warta Industri Hasil Pertanian, 1998)
The moisture sorption isotherm of fish cracker was determined experimentally. Variant water activity was applied for conditioning fish crackers' moisture content fish yield from these  conditions can be plotted to to describe their sigmoid sorption isotherm, which can determine primer and secondary water binding. This research also discussed the relationships among moisture content, crispness intensity and linear expansion. The results showed that the region between primer and secondary water binding for fish cracker are 7,54% and 15,33%. The maximum of its linear expansions is 229,78%, whereas the maximum of its crispness intensity is 1,65. The maximum expansion and cripness can be reached at the level of moisture content of 11,54%.